PENERAPAN TEKNOLOGI USAHATANI PADI SAWAH PADA KELOMPOK TANI SOKO MERAS DI KELURAHAN TARATARA SATU KECAMATAN TOMOHON BARAT KOTA TOMOHON - Aurelia Margaretha Kaparang; Noortje Marselianie Benu; Vicky Richard B. Moniaga (Sam Ratulangi University, 2020)
This study aims to determine the application of paddy farming technology in the Soko Meras farmer group in Taratara Satu Village, Tomohon Barat District, Tomohon City. This research was conducted in July - September 2019. Types of data used in this study are primary and secondary data. Primary data were collected from interviews conducted with all 13 members of the Soko Meras farmer group using a survey method (census) using a questionnaire. Secondary data is data obtained from the Statistics Office of Tomohon City. The results showed that the Soko Meras farmer group had applied agricultural technology in the paddy field farming. All members of the farmer group have implemented agricultural machinery such as tractors for land management, already applying the jajar legowo method in planting. Using sprayers to control pests and diseases. At the threshing stage of rice that has used threshing machines for harvesting. * eprm *